Diplomatic knowledge as National wisdom in Traditional Malay Literature - Noor Muhammad, Salmah Jan (Dewan Bahasa dan Pustaka, 2023)
Malay manuscripts are valuable documents that have records of the government and administration of a Malay Sultanate. Based on the records, there are various knowledge that can be searched as national wisdom. National wisdom is a collection of local knowledge that benefits the community, besides proving the intellectual peak of the past, which can be inherited by the community. Among the types of knowledge that are identified is diplomatic knowledge, which is knowledge of how a government manages its international affairs. The development of management and reinforcement of the stability of the Malay Sultanate is based on this relationship. The diverse sharing of organizational resources and natural materials made the relationship between two or more governments closer and based on mutual trust. However, diplomatic knowledge as national wisdom is still not fully explored in studies. Therefore, this article describes and analyzes diplomatic knowledge as national wisdom by using Hikayat Merong Mahawangsa as the material of discussion. As such, library methods and text analysis were used to achieve the objectives of the study. The results of this study showed that, on the whole, there is a form and method to handling diplomatic knowledge as national wisdom through selected manuscripts. This study can contribute knowledge to researchers in other related fields in order to utilize the data that have been recorded by previous authors in Malay manuscripts.